Analysis and optimisation of inventory management policies for perishable food products: a simulation study. (1st January 2014) - Bottani, Eleonora; Ferretti, Gino; Montanari, Roberto; Rinaldi, Marta
In this paper, we analyse three traditional reorder policies, namely economic order interval (EOI), economic order quantity (EOQ) and (S, s), applied to five food products with different shelf-life characteristics; three fresh products with limited shelf-life are considered. An ad hoc simulation model, reproducing a real two-echelon supply chain, was developed under Microsoft ExcelTM to simulate the product flow along the supply chain, according to the three policies. From the simulation, the minimum cost setting is first derived for all policies. Then, additional performance parameters (e.g., the throughput time of items) are computed and compared with the products constraints (e.g., the shelf-life), to assess the real suitability of implementing each policy to the products considered. Because both the supply chain modelled and the products data are derived from a real scenario, our outcomes should be of practical usefulness to inventory managers, to optimise inventory management of perishable products.